The Phenomenon of Personal Data as a “Pseudo Guarantee” In Fintech: Legal or Not? - Uswatun Hasanah; Djulaeka, Djulaeka; Murni, Murni; A. Zaenurrosyid (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
The study aims to examine the validity of personal data as a